Glucosamine inhibits IL-1β expression by preserving mitochondrial integrity and disrupting assembly of the NLRP3 inflammasome - Chiu, Hsiao-Wen; Li, Lan-Hui; Hsieh, Chih-Yu; Rao, Yerra Koteswara; Chen, Fang-Hsin; Chen, Ann; Ka, Shuk-Man; Hua, Kuo-Feng (Scientific reports, 2019)
The NLRP3 inflammasome promotes the pathogenesis of metabolic, neurodegenerative and infectious diseases. Increasing evidences show that the NLRP3 inflammasome is a promising therapeutic target in inflammatory diseases. Glucosamine is widely used as a dietary supplement to promote the health of cartilage tissue and is expected to exert anti-inflammatory activity in joint inflammation, which is a nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome-associated complication. Here, we investigated whether GlcN inhibits the NLRP3 inflammasome and dissected the underlying molecular mechanisms. We found that GlcN suppressed the NLRP3 inflammasome in mouse and human macrophages. A mechanistic study revealed that GlcN inhibited the expression of NLRP3 and IL-1β precursor by reducing reactive oxygen species generation and NF-κB activation in lipopolysaccharide-activated macrophages. GlcN also suppressed mitochondrial reactive oxygen species generation and mitochondrial integrity loss in NLRP3-activated macrophages. Additionally, GlcN disrupted NLRP3 inflammasome assembly by inhibiting NLRP3 binding to PKR, NEK7 and ASC. Furthermore, oral administration of GlcN reduced peritoneal neutrophils influx and lavage fluids concentrations of IL-1β, IL-6 MCP-1 and TNF-α in uric acid crystal-injected mice. These results indicated that GlcN might be a novel dietary supplement for the amelioration of NLRP3 inflammasome-associated complications.